2003
DOI: 10.1089/109662103768253669
|View full text |Cite
|
Sign up to set email alerts
|

Agitated Terminal Delirium and Association with Partial Opioid Substitution and Hydration

Abstract: Partial opioid substitution with fentanyl and moderate levels of hydration had no significant preventive effects on the occurrence of agitated delirium in the last week on a mass level. We should explore new strategies to prevent agitated delirium that are practically available in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 22 publications
0
44
0
5
Order By: Relevance
“…Some studies investigating the effectiveness of opioid rotation and hydration have found that hydration decreased myoclonus and sedation of dehydration [31], while hydration and opioid rotation decreased agitated delirium [37]. However, the latter finding was not confirmed by additional research [38], and beside, hydration did not improve delirium in the last few days of life [29]. The prevalence of hydration was similar, and opioid rotation was actively implemented in PCU.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies investigating the effectiveness of opioid rotation and hydration have found that hydration decreased myoclonus and sedation of dehydration [31], while hydration and opioid rotation decreased agitated delirium [37]. However, the latter finding was not confirmed by additional research [38], and beside, hydration did not improve delirium in the last few days of life [29]. The prevalence of hydration was similar, and opioid rotation was actively implemented in PCU.…”
Section: Discussionmentioning
confidence: 99%
“…29,60,68,90,[109][110][111][112][113][114][115][116][117] The concurrent use of antipsychotic medications targeted at perceptual disturbances or delusions may also be warranted.…”
Section: Irreversible Hyperactive Deliriummentioning
confidence: 99%
“…[47][48][49][50][51] In dying patients with hyperactive delirium, when the goals are to decrease agitation, relieve muscle tension, ensure amnesia, and minimize the risk of seizures, benzodiazepines appear to be ideal medications to manage and prevent these symptoms. 29,60,68,90,[109][110][111][112][113][114][115][116][117]119 Benzodiazepines. These function as sedatives, anxiolytics, skeletal muscle relaxants, amnestics, and potent antiepileptics (Table 3).…”
Section: Muscle Relaxation Anticonvulsantmentioning
confidence: 99%
“…Respecto a los efectos adversos, en general se ha ido describiendo un mejor perfil que otros analgési-cos opioides en cuanto a efectos clínicamente importantes (depresión respiratoria, estreñimiento, mareos, psicosis...) 15 . Por sus características farmacocinéticas 6,12 , bajo peso molecular y alta lipofilia, se absorbe a través del tejido celular subcutáneo pasando directamente a la circulación sanguínea, evitando el primer paso hepático.…”
Section: Discussionunclassified